On‐treatment gamma‐glutamyl transferase predicts the development of hepatocellular carcinoma in chronic hepatitis B patients. (29th November 2021) - Huang, Chung‐Feng; Jang, Tyng‐Yuan; Jun, Dae Won; Ahn, Sang Bong; An, Jihyun; Enomoto, Masaru; Takahashi, Hirokazu; Ogawa, Eiichi; Yoon, Eileen; Jeong, Soung Won; Shim, Jae‐Jun; Jeong, Jae Yoon; et al.
Abstract: Background & Aims: Gamma‐glutamyl transferase (GGT) has been predictive of chronic hepatitis C‐related hepatocellular carcinoma (HCC) development. Its role in the risk of HCC in chronic hepatitis B (CHB) patients treated with nucleotide/nucleoside analogues (NAs) is elusive. Methods: A total of 2172 CHB patients from East Asia were randomized into development and validation groups in a 1:2 ratio. Serum GGT levels before and 6 months (M6) after initiating NAs and the potential risk factors were measured. The primary endpoint was HCC development 12 months after NA initiation. Results: The annual incidence of HCC was 1.4/100 person‐years in a follow‐up period of 11 370.7 person‐years. The strongest factor associated with HCC development was high M6‐GGT levels (>25 U/L; hazard ratio [HR]/95% confidence interval [CI]: 3.31/2.02‐5.42, P  < .001), followed by cirrhosis (HR/CI: 2.06/1.39‐3.06, P  < .001), male sex (HR/CI: 2.01/1.29‐3.13, P  = .002) and age (HR/CI: 1.05/1.03‐1.17, P  < .001). Among cirrhotic patients, the incidence of HCC did not differ between those with high or low M6‐GGT levels ( P  = .09). In contrast, among non‐cirrhotic patients, the incidence of HCC was significantly higher for those with M6‐GGT level >25 U/L than for their counterparts ( P  < .001). Cox regression analysis revealed that the strongest factor associated with HCC development in non‐cirrhotic patients was high M6‐GGT levels (HR/CI: 5.05/2.52‐10.16, P  < .001), followed by age (HR/CI: 1.07/1.04‐1.09, P  < .001). Non‐cirrhotic elderly patients with high M6‐GGT levels had a similarly high HCC risk as cirrhotic patients did ( P  = .29). Conclusions: On‐treatment serum GGT levels strongly predicted HCC development in CHB patients, particularly non‐cirrhotic patients, treated with NAs.